Clinical characteristics and diagnostic aspects of cervicogenic dizziness in patients with chronic dizziness: A cross-sectional study. (August 2022) - De Vestel, Charlotte; Vereeck, Luc; Van Rompaey, Vincent; Reid, Susan A.; De Hertogh, Willem
Abstract: Background and objectives: Chronic dizziness can significantly affect quality of life, but identifying the underlying cause remains challenging. This study focuses on proprioceptive cervicogenic dizziness (CGD) and aims: (1) to compare clinical test results between patients with CGD, dizzy patients without CGD, and healthy controls; and (2) to evaluate the diagnostic value of the clinical tests for CGD in patients with chronic dizziness. Methods: Sixty patients with chronic dizziness (18 with CGD and 42 without CGD), and 43 healthy controls underwent clinical tests evaluating neck function (mobility, proprioception, muscle function and disability), balance control, and the presence of visually induced dizziness. Data were analysed through one-way ANOVA, chi-square, independent samples t -test, and logistic regression analyses. Results: Patients with CGD had significantly more neck pain-related disability (Neck Bournemouth questionnaire (NBQ), p = 0.006), but better static (Static Balance, p = 0.001) and dynamic balance (Tandem Gait, p = 0.049), compared to dizzy patients without CGD. Univariable analyses revealed that increased NBQ (OR 1.05 [1.01; 1.09], p = 0.017), Joint Position Error (JPE) after extension (OR 1.52 [1.00; 2.32], p = 0.050), and Tandem Gait scores (OR 1.09 [1.01; 1.18], p = 0.046) were individually associated with higher odds of having CGD. Their optimal cut-off level (based on the maximum Youden index) had high sensitivity but low specificity for CGD. The multivariable model, including NBQ and Tandem Gait, had fair discriminative ability (AUC = 0.74, 95% CI [0.61; 0.87]). Conclusion: The combined use of the NBQ and Tandem Gait tests had the highest discriminative ability to detect CGD in patients with chronic dizziness. Highlights: Diagnosing CGD in patients with chronic dizziness remains a challenge. Positive correlation between CGD and JPE after extension, NBQ, Tandem Gait separately. JPE after extension, NBQ, and Tandem Gait had high sensitivity but low specificity. Combining NBQ and Tandem Gait improves CGD detection in chronically dizzy patients.